Pengaruh Konsentrasi Polietilen glikol terhadap Warna, Transmisi Cahaya dan Transparansi Film Edibble Film dari Gelatin Usus Ayam - Garnesah, Asih; Wulandari, Eka; Gumilar, Jajang (Jurnal Teknologi Hasil Peternakan, 2023)
Edible film is a packaging made of biodegradable materials from gelatinized chicken intestinal protein. Gelatin is a protein macro molecule that has hydrocolloid properties, can form a thin elastic layer, form a transparent and strong film. Plasticizers are needed in making edible films so that they become more elastic and not easily brittle. Plasticizers such as polyethylene glycol (PEG) are usually added to edible films. The purpose of this research was to determine how the color, light transmission, and transparency of edible film made from broiler intestinal gelatin were affected by various concentrations of polyethylene glycol. The method used was experimental using a completely randomized design (CRD) with 5 treatments of PEG concentration (P1=10%, P2=20%, P3=30%, P4=40%, P5=50%). Each treatment was repeated as many as 4 replicates, with observed parameters of color, light transmission and film transparency. The results showed that the PEG treatment had a significant effect (P<0.05) with the best concentration of 30% which resulted in color L* 30.10, a* 29.69, b* 0.70, light transmission 200- 800nm 0.61 to 44.66 and film transparency 2.39 with a film thickness of 0.18mm